2002
DOI: 10.1029/2001jd000867
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cl2 formation from aqueous NaCl particles: Evidence for interfacial reactions and importance of Cl2 decomposition in alkaline solution

Abstract: [1] A series of experiments have demonstrated that a significant yield of chlorine gas is produced when mixtures of ozone and sodium chloride particles above their deliquescence point are irradiated at 254 nm. In order to obtain expressions for future modeling studies, a comprehensive model is used to analyze the system and to determine its sensitivity. This work reexamines and expands previous studies [Knipping et al., 2000]. The enhanced model, described in detail herein, reaffirms that current known physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 159 publications
(224 reference statements)
2
92
1
Order By: Relevance
“…Other work suggests that the reaction of hydroxyl radicals (OH • ) at the particle surface more accurately depicts the chemistry active during heterogeneous Cl2 production [30,33,34], where the formation of a surface complex between particulate Cl − and gas phase OH • was suggested as the rate limiting step, as is shown in Reactions (R3) and (R4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work suggests that the reaction of hydroxyl radicals (OH • ) at the particle surface more accurately depicts the chemistry active during heterogeneous Cl2 production [30,33,34], where the formation of a surface complex between particulate Cl − and gas phase OH • was suggested as the rate limiting step, as is shown in Reactions (R3) and (R4).…”
Section: Introductionmentioning
confidence: 99%
“…Such a Cl2 source could potentially lead to the enhanced oxidation of CH4 and other VOCs [23,25,58], and therefore enhanced formation of secondary organic aerosol. Additionally, enhanced O3 production can result from the presence of a Cl • source [1,33]. The implications of this are discussed further in Section 3.4.…”
Section: Cl2 Measurementsmentioning
confidence: 99%
“…Rates are given in parts per billion per second at 298 K and rate constants for calculations are from Manion et al [115] Cl and [5] Aschmann and Atkinson, [15] Finlayson-Pitts et al, [109] Stutz et al, [110] Gill and Hites, [111] Atkinson et al [112] and Aschmann et al [113] A mechanism involving the formation of a surface complex between particulate chloride and OH (OH?Cl À ) (Reactions 20, 21) has been proposed to explain the processes involved in Reaction 14. [41,42] OH ðgÞ þ Cl…”
Section: Heterogeneous and Multiphase Chlorine Chemistry Mechanismsmentioning
confidence: 99%
“…As possible explanation, Sadanaga et al [2001] suggested heterogeneous reaction of ozone with sea salt in the presence of ferric ions. Another possibility for the production of Cl 2 would be the reaction between OH and Cl À on aerosol surfaces [Knipping et al, 2000;Knipping and Dabdub, 2002], in addition to the autocatalytic mechanism involving oxidation of Cl À by HOCl/HOBr in acidified sea salt aerosol [e.g., Sander and Crutzen, 1996;Vogt et al, 1996]. Using a similar method as Spicer et al [1998], Finley and Saltzman [2006] measured Cl 2 in coastal urban air in Irvine, California, reporting mixing ratios up to 20 pmol mol À1 with a 2-month average of 3.5 pmol mol À1 .…”
Section: Introductionmentioning
confidence: 99%